The female protagonist’s intersection with the African world of actuality in Beyala’s novel Tu t’appelleras Tanga - Glaeser, Jessica (WritingThreeSixty, 2019)
In order to overcome the silence that had been instilled by colonial-ism, several postcolonial female writers employ fiction to restore their local culture and reflect on their representation in historical writings. For female writers, literature often becomes a medium through which they can become active agents of their own destiny by establishing a voice for themselves. Writing becomes a means of reclaiming traditional discourses relating to women. The following study is primarily focused on Calixthe Beyala, a Cameroonian novelist, and specifically concentrates on the manner in which Beyala makes use of her female protagonist in Tu t'appelleras Tanga to portray the realities facing African Francophone females. The study aims at illustrating that the female protagonist plays a critical role in mirror-ing both the conditions of females in African societies and the conditions pertaining to Womanism in a universal context. Through the role of the protagonist, the study reveals that there seems to be some relationship between fiction and society which is definitely enough for fictional characters to be used as prototypes for social roles and attitudes. In order to further investigate the manner in which African actualities are able to exist in fictional narratives, the study draws an extensive comparison between the fictional narrative Tu t'appelleras Tanga and selected non-fictional Cameroonian laws ranging from 1980 to 2017. By addressing the intentions of fictional narratives, the study reveals a possible association between Beyala's fiction and the African world of actuality relative to the African females' predicament that is associated with patriarchal dominance, prostitution, the lack of agency as well as economic exploitation. To conclude, the paper maintains that Francophone African female novelists, and in particular, Beyala, make use of fictional narratives to not only highlight the pivotal issues regarding the status of African women but also creates a voice for future female generations to become empowered through the act of narration.